PENGARUH MEDIA AUDIO VISUAL TERHADAP KETERAMPILAN DAN KESENANGAN BELAJAR PENCAK SILAT SENI TUNGGAL TANGAN KOSONG PADA SISWA PUTRA DI SEKOLAH MENEGAH PERTAMA NEGERI 12 BANDUNG - Deka Ayu Wulandai, - (2022)
Deka Ayu Wulandari (1902180). The Influence of Audio Visual Media on the Skills and Enjoyment of Learning Pencak Silat, the Art of Single Handed Empty Arts. Paper, Health and Recreation Physical Education Study Program, Department of Sports Education, Faculty of Sports and Health Education, University of Education Indonesia, Bandung 2022. This study aims to determine the effect of audio-visual media on the skills and enjoyment of learning the empty-handed single-handed martial art of pencak silat in male students at SMP Negeri 12 Bandung. The method used in this study is an experimental method with the type of pre test and post test design. The population in this study were 10 male students who took part in silat extracurricular activities at SMP Negeri 12 Bandung. While the sample used in this study were 10 male students who took part in silat extracurricular activities at SMP Negeri 12 Bandung. The instruments used in this study were scoring sheets or single category assessment drafts of pencak silat and questionnaires in understanding pleasure. Based on the results of the research that the authors conducted as well as the calculation and analysis of data from the measurement results, in this section the authors can put forward the following conclusions after being given audio-visual media treatment it provides a significant increase in the skills and pleasure of learning empty-handed single-handed martial arts in male students at SMPN 12 Bandung.